L’agriculteur gitan ou voyageur comme impensé institutionnel. Discriminations et injustices dans l’accès à la terre agricole et au statut d’agriculteur - Coline Perrin; Gaëlla Loiseau; Charles Lugiery; Guillaume Lacquement (Développement Durable et Territoires)
This article looks at how Gypsies and Travelers access to land and to the status of farmer. It is based on surveys of gypsy families in Occitanie region, and of farmers and representatives of institutions controlling access to agricultural land or building rights. Our findings reflect institutional representations of different ways of living and producing, considered deviant. They bear witness to discrimination in access to land, and to forms of social exclusion, felt by Gypsies and Travelers as injustices. The invisibility of their farming activities hinders their access to the status of farmer, while the stigmatization of their way of life hinders the survival of their activity. The significance of these findings is discussed in the light of current issues surrounding habitability, in a context of ecological and climatic urgency.